Chest Radiography and CT scan as Predictor Factors for Long COVID - Reny Luhur Setyani; Srie Retno Endah; Ana Madjawati; Muhammad Hafiz; Rahma Ayu Larasati; Turwuri Handayani; Khatarina Setyawati; Farsida Farsida (Jurnal Respirologi Indonesia, 2023)
Background: Long COVID presents a significant challenge in the management of COVID-19 patients, necessitating risk stratification and early intervention to mitigate its impact.Objective: This retrospective cohort study aimed to establish a predictive link between initial clinical assessments and imaging findings upon COVID-19 diagnosis and the subsequent development of long COVID symptoms at 6-8 weeks post-treatment.Methods: The study analyzed chest radiography images utilizing the Brixia Score and chest CT scans employing the Severity Score at the time of COVID-19 diagnosis. These findings were then compared with the presence of long COVID symptoms.Results: Among 54 study participants, 63% were non-elderly and 37% were elderly, with a nearly equal gender distribution. Notably, 74.1% of patients developed long COVID symptoms. The Brixia Score identified 38.9% as mild, 37% as moderate and 24.1% as severe lung involvement. Correspondingly, the Severity Score from chest CT scans revealed 33.3% with mild, 53.7% with moderate, and 13% with severe lung abnormalities. Statistical analysis confirmed strong correlations between both the Brixia Score (r = 0.553) and the Severity Score (r = 0.733) with the development of long COVID symptoms (p = 0.000).Conclusion: This study underscores the significant predictive value of both the Brixia Score and the Severity Score in identifying COVID-19 patients at risk of developing long COVID. These findings have critical implications for early risk stratification and targeted intervention strategies to prevent long COVID's debilitating effects.